A REVIEW STUDY ON THE EFFECT OF ORAL CURCUMIN ON BREAST CANCER WITH THE REFERENCE OF CLINICAL AND BIOCHEMICAL MARKERS - Pandey, Priya; Tyagi, Shaily; Pandey, Mukesh (International Journal of Research -GRANTHAALAYAH, 2025)
As one of the most common cancers in the world, breast cancer requires ongoing studies into efficient treatment approaches. The polyphenol curcumin, which comes from Curcuma longa, has attracted a lot of attention because of its possible anti-cancer effects. This review assesses the impact of oral curcumin on biochemical markers and clinical factors related to breast cancer. To evaluate curcumin's effects on tumour growth, oxidative stress, inflammatory markers, and patient survival outcomes, we look at preclinical and clinical research. Breast cancer is a complex illness that is impacted by environmental, hormonal, and hereditary variables. Currently available therapeutic options include radiation, chemotherapy, surgery, and targeted medicines; nevertheless, these methods frequently have serious adverse effects. Curcumin is a prospective adjuvant therapy for the treatment of breast cancer because of its anti-inflammatory, antioxidant, and anti-proliferative qualities, which have been studied. The effectiveness of oral curcumin in modifying the biochemical and clinical indicators linked to breast cancer is examined in this review. In order to enhance patient outcomes, new adjunct medicines must be investigated because breast cancer continues to rank among the world's leading causes of cancer-related mortality. The bioactive polyphenol curcumin, which comes from Curcuma longa, has drawn a lot of interest because of its anti-inflammatory, antioxidant, and anticancer qualities. This study evaluates clinical characteristics and biochemical markers in preclinical and clinical research to investigate the impact of oral curcumin supplementation on breast cancer. There is evidence that curcumin inhibits metastasis, reduces angiogenesis, and induces apoptosis via modulating important molecular pathways such as PI3K/Akt, NF-κB, and MAPK signaling. Curcumin has also been shown to reduce oxidative stress markers, tumor biomarkers like CA 15-3 and CEA, and inflammatory cytokines like IL-6 and TNF-α. There are still issues with its absorption and the best ways to dose it, despite clinical trials showing encouraging outcomes in terms of enhancing patient quality of life and slowing tumor growth. Subsequent investigations ought to concentrate on augmenting curcumin's medicinal effectiveness via sophisticated formulations and combination treatments.